EKSPLORASI TANTANGAN INTEGRASI MEDIA PEMBELAJARAN MATEMATIKA DI KELAS V SEKOLAH DASAR: PENDEKATAN STUDI KASUS DI SDN 2 NGEPEH - Aulia Nurfadilah; Zahra Salsabila; Nanda Dwi; Widad Nayla; Fachri Rahmanda; Beti Istanti Suwandayani (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to examine the obstacles to the application of mathematics teaching media in grade V of SDN 02 Ngepeh, particularly in the topics of multiplication and division. The background is the low mastery of basic arithmetic concepts, so that students often have difficulty answering questions, especially story problems. The method used was a case study with data collection through classroom observation, interviews with teachers and students, and document analysis. The findings show that even though teachers have used approaches such as material reinforcement, gradual practice, and personal guidance, the use of teaching media has not been maximized. The main challenges include teachers' limited skills in designing appropriate media, a lack of diverse, engaging teaching tools, and inadequate classroom facilities. Students appear very enthusiastic when using concrete media, visuals, and educational games that facilitate understanding of abstract concepts. This study emphasizes the need to improve teachers' abilities to create innovative media and select more effective interactive methods. The main recommendation is for teachers and schools to collaborate to develop creative teaching media to improve the quality of mathematics learning at the elementary level.